Too close to home - Glass, Seraphina Nova (Park Row Books, 2026)
"Those lucky enough to live in the elite lakefront community of Cloverhill Lakes are drawn to it for its safety and top-notch school district. The moms meet for coffee at the park while their kids play, they're heavily involved in the PTA, and the summers are filled with chardonnay, brunch, sundresses, and backyard bonfires. But everything changes when Regan Hoffman's car explodes at the annual Labor Day party. The wrong person is killed, but it was meant for her. As the carefully crafted walls of her community begin to crumble, Regan tries to keep it together--something made infinitely harder when she sees her dead husband...alive. When a Cloverhill Lakes resident suddenly goes missing, dark secrets begin to surface from underneath the idyllic veneer of their beautiful community--and the truth threatens to destroy them all as Regan finds herself in a fight for her life." -- Provided by publisher